Konsep Percaya Diri dalam Al-Qur'an Sebagai Upaya Pembentukan Karakter Bangsa - huda, nur (Ali Muchasan, 2016)
Problem: How is Concept of self-confidence in Al-Qur’an to efforts maker characteristic the nation? The Objective of Research: To find out how Concept of self-confidence in Al-Qur’an to efforts maker the nation characteristic. The purpose of research: The result of research is expected to be able to be a basic of theory and philosophy of Concept of self-confidence to maker the nation characteristic that will be applied in practical level. The procedure of research: The method used in this research is using descriptive qualitative approach. The type of this research is library research. The instrument of this research is the researcher himself. The object of this research is al-qur’an and bound up other sources book with this thesis title. The data analyst is using analyst content. Result of the research: Self-Confidence Holly al-qur’an is the first references explain about self-confidence clearly. With positif belief can increase maker the nation characteristic